2019
DOI: 10.1161/circresaha.118.314571
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Peptidylarginine Deiminase IV Promotes VWF-Platelet String Formation and Accelerates Thrombosis After Vessel Injury

Abstract: Rationale: PAD4 (peptidylarginine deiminase type IV), an enzyme essential for neutrophil extracellular trap formation (NETosis), is released together with neutrophil extracellular traps into the extracellular milieu. It citrullinates histones and holds the potential to citrullinate other protein targets. While NETosis is implicated in thrombosis, the impact of the released PAD4 is unknown. Objective: This study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 68 publications
3
80
0
2
Order By: Relevance
“…Remarkably, LL37 is also prone to citrullination, which decreases its antimicrobial efficiency [178]. Sorvillo et al demonstrate in an elegant study that PAD4-catalyzed citrullination of ADAMTS 13 decreases its catalytic efficiency [179], which in vivo might result in increased half-life of vWF multimers that predispose to thrombosis.…”
Section: Pads-whose Weapon Are They Really?mentioning
confidence: 99%
“…Remarkably, LL37 is also prone to citrullination, which decreases its antimicrobial efficiency [178]. Sorvillo et al demonstrate in an elegant study that PAD4-catalyzed citrullination of ADAMTS 13 decreases its catalytic efficiency [179], which in vivo might result in increased half-life of vWF multimers that predispose to thrombosis.…”
Section: Pads-whose Weapon Are They Really?mentioning
confidence: 99%
“…Both of these conditions could be attributed to an impairment of UL‐VWF cleavage by ADAMTS13 . Recently, it was reported that endogenous ADAMTS13 activity is reduced when the enzyme is citrullinated by PAD4, which remains active after its release from neutrophils in processes such as NETosis . Therefore, preventing NETosis or inhibiting PAD4 may also protect burn patients from developing burn‐induced thrombotic microangiopathies.…”
Section: Discussionmentioning
confidence: 99%
“…In 1971, it was first identified that the decrease of vWF could cause the occurrence of hemorrhagic diseases and, with the continuous studies on vWF, it was shown that the increase of vWF could promote the formation of thrombosis. vWF is synthesized by vascular endothelial cells and marrow megakaryocytes, which can connect collagen and platelets, initiate the coagulation process, and play a bridging role in thrombus. Jukic et al .…”
Section: Discussionmentioning
confidence: 99%